Socio-linguistic research of the dialect of Preševo in the South of Serbia - Trajković, Tatjana (Baltistica, 2016)
This paper shows the results of the research of the dialect of Preševo, a small town in the south of Serbia. Since social and urban dialectology and socio-linguistic methods of research in Serbian linguistics are new, a theoretical consideration is given first. Then the methods used in processing the material from the dialect of Preševo are explained. The implication scales and diagram which show the level of representation of dialectological features in relation to the standard features are shown too. The conclusion is that the dialect in this city has the features of the standard Serbian language and it is exactly how it is distinguished from the dialect of the villages.